Air pollution and cardiovascular disease: a systematic review of the effects of air pollution, including bushfire smoke, on cardiovascular disease - Fariha Islam; Sai Keerthana Nukala; Pallavi Shrestha; Tim Badgery-Parker; Fiona Foo (American Heart Journal Plus)
Objective: Particulate matter (PM) with diameter ≤ 2.5 μm (PM2.5) and ≤ 10 μm (PM10), including from bushfire smoke, is associated with cardiovascular disease (CVD) morbidity and mortality. This systematic review assesses how CVD morbidity and mortality is affected by type, duration, and level of air pollution exposure. Data sources: A search was conducted on Ovid Medline, Embase and Scopus, spanning across 1 January 2012 to 30 July 2022. Primary quantitative studies exploring the effect of PM2.5, PM10 or bushfire smoke on CVD were included. Studies without adjustment for confounding factors were excluded. The Newcastle-Ottawa Scale was used to assess the risk of bias (ROB) in the studies, and meta-analysis was conducted on relevant outcomes. Findings: A total 275 studies were obtained, and 80 studies were analysed with diseases ranging from ICD-10 I00-I99. For CVD morbidity, increased PM2.5 and PM10 was associated with 1.92 (95 % CI: 0.58,3.26) years of life lost per 10 μg/m3 increase in exposure. Increased PM2.5 and PM10 was associated with a 0.52 % (95 % CI: 0.37,0.68) increase in mortality per 10 μg/m3 increase in exposure. Bushfire smoke also presented similar trends. Two studies had high ROB, 42 had medium ROB, and 36 had low ROB. There was high heterogeneity between the studies, with I2 values ranging between 88.09 % and 94.25 %. Conclusion: Air pollution including bushfire smoke is associated with increased CVD morbidity and mortality. This effect ranges across different types, durations, and levels of air pollution exposure, making stringent climate change and air pollution mitigation strategies imperative.